Sink strength, nutrient allocation, cannabinoid yield, and associated transcript profiles vary in two drug-type Cannabis chemovars - Jost, Ricarda (Journal of experimental botany, 2025)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.